Hubungan Antara Harga Diri dan Dukungan Sosial dengan Kesejahteraan Subjektif pada Siswa MTs Yang Tinggal di Pondok Pesantren - Ayu Nurmalitasari; Rahma Widyana (Neolectura, 2021)
This study was aimed to determine 1) the relationship between self-esteem and social support with subjective well-being in MTs students who live in Islamic boarding schools; 2) the relationship between social support and subjective well-being of MTs students living in Islamic boarding schools; 3) the relationship between self-esteem and social support with subjective well-being in MTs students living in Islamic boarding schools. This study involves one dependent variable, namely subjective well-being and two independent variables that influence it, namely: self-esteem and social support. There are 193 subjects in this study. The research subjects are students of MTs Darussholihin Yogyakarta who study at the same time living in Islamic boarding schools. The data collection method used a Likert scale and data analysis using product moment correlation. The effective contribution between self-esteem and social support for MTs students who live in Islamic boarding schools is 0.573 or 57.3% is explained by the variables of self-esteem and social support, while the remaining 42.7% is explained by other variables